Integrated pest management in turf - Clokey, Joe; Harrigan, Jim; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2004)
Four programs covering integrated pest management theory and practice in four major areas: turf, landscape, greenhouses and agriculture
Title from title screen
DVD format
Keywords: Pests -- Integrated control; Agricultural pests -- Integrated control; Turfgrasses -- Diseases and pests -- Integrated control; Turf management